MMS Observations of Electron Vorticity in the Earth’s Magnetosheath - Li, Yijun; Yuan, Zhigang; Huang, Shiyong; Jiang, Kui; Wu, Honghong (The Astrophysical journal, 2024)
The Earth’s magnetosheath serves as a natural laboratory to study the transition of highly turbulent fluctuations. The fundamental information about plasma turbulences can be examined observationally with the help of electron vorticity measurements. This study presents the first statistics of the electron vorticity field in the magnetosheath by utilizing 4 yr data from NASA’s Magnetospheric Multiscale mission. In this study, the magnetosheath vorticity has a dominant perpendicular anisotropy. The vorticity field in the subsolar region is much stronger than that of magnetosheath flanks. Clear dusk-favored asymmetry for large vorticity is identified in the subsolar region. We examine that the electron flow vorticity in the turbulent magnetosheath is well anticorrelated with the electron density. The vorticity is of great importance in energy dissipation and electron heating in the magnetosheath flanks. This study can improve the current understanding of electron vorticity due to its ubiquitous role in space plasma turbulences.